Divisi Content Creator Dalam Mendukung Inovasi Layanan Digital Perpustakaan Universitas Muhammadiyah Yogyakarta - Yuliana Ramawati; Eko Kurniawan; Muhamad Jubaidi; Muhkamad Fatori (IAIN Ponorogo, 2022)
This study aims to provide an overview of the formation of the content creator division (Librarian) in the UMY Library, what steps are taken to develop the creativity of content creator librarians and the content that has been produced to support digital service innovation. The method used in this research is descriptive qualitative. The results show that the efforts made at the UMY library in order to develop librarian creativity include; through the implementation of video editing workshops, workshops on using Canva, participating in library promotion training, participating in webinars with similar topics. The librarian's innovative products in creating digital content include various videos, podcasts, website creation for Indonesian librarian organizations, TikTok content, Instagram, Youtube and other social media services. The variety of products produced proves that UMY librarians are able to innovate in line with the needs and developments of the times through developing the competence of librarians as content creators.